Tuned acidic properties of hmor@kcc-1 for enhanced n-hexane isomerization - M., Ibrahim; A. A., Jalil; S., Triwahyono; M. Y., S. Hamid; Y., Gambo; A. A., Abdulrasheed; Herma Dina, Setiabudi (2018)
Fibrous silica encapsulated mordenite zeolite (HMOR@KCC-1) was prepared by using microemulsion system coupled with zeolite crystal-seed crystallization technique. While the activity of the catalysts were tested for n-hexane isomerization in a microcatalytic pulse reactor. XRD analysis shows reduction of modernite crystallinity phase due to silica encapsulation. IR studies of pyridine adsorption gave the concentration of both Brönsted acid sites (BAS) and Lewis acid sites (LAS). 2,6- Lutidine as probe molecule showed that Pt/HMOR contains strong Brönsted acid sites while Pt/HMOR@KCC-1 contains medium strength Brönsted acid sites. The relatively mild acid sites and improved acid sites accessibility introduced by the fibrous silica morphology enhanced the catalytic yield of Pt/HMOR@KCC-1 by 22% compared to Pt/HMOR in isomerization of n-hexane.